Design de interação em jogos digitais: análise da mecânica estrutural em smartphones - NEHME, Laís Soares (2022)
Digital games are popular entertainment products worldwide. Throughout its evolution, some categories of these games gained operational complexity by adding new game actions, which was reflected in their controls that have more and more keys or action buttons. In the case of smartphone games, it is necessary to share a small screen to display the game's graphic elements and input the player's actions, which can generate usability problems. This work, with an analytical-descriptive character and a qualitative approach, aimed to analyze the structural mechanics of digital games on smartphones in order to promote better interaction with users, in the light of the Interaction Design literature. It describes the methodological steps of: selection of game genre for study, inspection of game interfaces, application of usability tests of games and discussion of the problems found. The results include a description of the types of mechanics that are frequent in the game genre studied, the usability problems identified from the systematic observation of the interaction of participants with the games and, finally, guidelines for the design of game interaction are carried out. of the genre studied.